Prohibited Speech Acts in Indonesian Bugis Makassar Dialect for Students of the Department of Indonesian Literature, Hasanuddin University - Andi Meirling (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This research aims to describe the speaking strategies of Indonesian Literature Department students, and to analyze prohibited speech acts in Indonesian Bugis Makassar dialect for students. This research is a quantitative descriptive research with pragmatic studies. The data source in this research is students from the Department of Indonesian Literature, Hasanuddin University, from the Bugis-Makassar tribe. Data was obtained through distributing questionnaires to respondents. The research results show that the speaker/partner is older and more  familiar. The most widely used strategies are STT, SKN, SSS, SKP. The speakers/interlocutors are older and less familiar, SKN, STT, SSS, and SKP. Younger and more familiar speakers, STT, SKN, SSS, and SKP. Younger and less familiar speakers, STT, SKN, SSS, SKP. If the speakers are the same age and are not familiar, STT, SSS, SKN, and SKP and if the speakers are the same age and are not familiar, STT, SKN, SSS, SKP. However, the strategy of younger and unfamiliar partners and speakers of the same age who are not familiar are still considered impolite or low in politeness, resulting in a shift in norms because the strategy most often used by teenagers in expressing something is the strategy of being frank without further ado so that the speaker loses face and this makes his politeness low.